Harvest the rain - TVE International
In the arid lands of West Kenya, the seminomadic Turkanas practise r`ainwater harvesting'. This simple desert technique improves sorghum crop yields, giving a surplus to see the Turkanas through periods of drought, and a source of income to build up their goat herds.